Penerapan Metode Multi Games Dalam Pembelajaran Mufrodat Di LKP Ibnu Khaldun Driyorejo Gresik - Sholihudin Al-Ayyubi (FATAWA: Jurnal Pendidikan Agama Islam, 2021)
This article is the result of a study that describes the stages in the application of the multigames method in Arabic mufradat learning by adding vocabulary intensely to each meeting. LKP Ibnu Khaldun is an Arabic language development institution by applying the multigames method which refers to an independent guidebook entitled "The Smart Book of Memorization of Arabic-English Vocabulary for Children" which contains mufradat themes and alternative language games along with the steps. This type of research is a field research with a qualitative approach. Methods of data collection by observation, interviews and documentation with data analysis techniques using descriptive qualitative. Based on the results of the study, there were several themes taught by the tutor in six meetings, including riyadhah (sports) by applying the traditional game of gobak sodor, naqlun (transportation) with the traditional engkle game, al-ma'kulat (food) with a crossword puzzle (TTS) game. Crossword puzzles), alwanun (colors) with treasure hunting games, al-hayawanat (animals) with word-matching games and their meanings, fi al-sama' (objects in the sky) with traditional games of dolip. All students feel excited and always look forward to every game in one meeting, especially if there is a reward from the tutor.